To solve the system of equations using the elimination method, we can multiply the second equation by 4 to get the coefficients of y to be the same:
4(x+3y) = 4(-10)
4x + 12y = -40
Now, we can subtract the first equation from the second equation:
(4x + 12y) - (3x - 4y) = -40 - (-4)
4x + 12y - 3x + 4y = -40 + 4
x + 16y = -36
Now we have a new equation:
x + 16y = -36
We can solve this equation for x:
x = -36 - 16y
Now we can substitute this expression for x into either of the original equations. Let's use the first equation:
3x - 4y = -4
3(-36 - 16y) - 4y = -4
-108 - 48y - 4y = -4
-108 - 52y = -4
-52y = -4 + 108
-52y = 104
y = 104/-52
y = -2
Substituting the value of y back into the expression for x:
x = -36 - 16(-2)
x = -36 + 32
x = -4
Therefore, the solution to the system of equations is (-4, -2).
Solve the following system of equations using the elimination method.
3x−4y=−4 , x+3y=−10
(1 point)
Responses
(−4,−2)
left parenthesis negative 4 comma negative 2 right parenthesis
(−16,2)
left parenthesis negative 16 comma 2 right parenthesis
(−16,−2)
left parenthesis negative 16 comma negative 2 right parenthesis
(−2,−4)
left parenthesis negative 2 comma negative 4 right parenthesis
1 answer